Aneurysm Treatment With Woven EndoBridge in the Cumulative Population of 3 Prospective, Multicenter Series: 2-Year Follow-Up. Issue 2 (20th January 2020) - Pierot, Laurent; Moret, Jacques; Barreau, Xavier; Szikora, Istvan; Herbreteau, Denis; Turjman, Francis; Holtmannspötter, Markus; Januel, Anne-Christine; Costalat, Vincent; Fiehler, Jens; Klisch, Joachim; Gauvrit, Jean-Yves; et al.
Abstract: BACKGROUND: Woven EndoBridge (WEB; Sequent Medical) treatment is an innovative endovascular approach for treatment of wide-neck bifurcation aneurysms. Initial studies have shown high safety with good efficacy at short term confirmed by trials conducted in United States (WEB-Intrasaccular Therapy) and in Europe (WEB Clinical Assessment of Intrasaccular Aneurysm Therapy [WEBCAST], French Observatory, and WEBCAST-2). OBJECTIVE: To report the 2-yr clinical and anatomical results of WEB treatment in the combined population of 3 European trials. METHODS: In a French Observatory, 2-yr clinical and anatomical data were collected. In WEBCAST and WEBCAST-2, 2-yr follow-up was optional, and data were collected when follow-up was performed. Aneurysm occlusion was evaluated using a 3-grade scale: complete occlusion, neck remnant, and aneurysm remnant. RESULTS: The population for safety was 138/168 patients (82.1%), including 89 females (64.5%), with mean age of 55.5 ± 10.2 yr. The population for efficacy was 121/169 aneurysms (71.6%). Aneurysm locations were middle cerebral artery in 65/121 aneurysms (53.7%), anterior-communicating artery in 25/121 (20.7%), basilar artery in 17/121 (14.0%), and internal carotid artery terminus in 14/121 (11.6%). No clinically relevant adverse events occurred between years 1 and 2. At 2 yr, complete occlusion was observed in 62/121 (51.2%) aneurysms, neck remnant in 36/121 (29.8%) aneurysms, and aneurysm remnant in 23/121 (19.0%) aneurysms. The global retreatment rate at 2 yr was 9.3%. CONCLUSION: This analysis confirms the high safety profile of WEB treatment at 2 yr. Aneurysm occlusion is generally stable at 2 yr, and the retreatment rate between 1 yr and 2 yr is low (2.0%). Graphical Abstract: